Perovskite Light‐Emitting Diodes: High‐Performance Blue Perovskite Light‐Emitting Diodes Enabled by Efficient Energy Transfer between Coupled Quasi‐2D Perovskite Layers (Adv. Mater. 1/2021). Issue 1 (4th January 2021) - Ren, Zhenwei; Yu, Jiahao; Qin, Zhaotong; Wang, Jing; Sun, Jiayun; Chan, Christopher C. S.; Ding, Shihao; Wang, Kai; Chen, Rui; Wong, Kam Sing; Lu, Xinhui; Yin, Wan‐Jian; et al.
Abstract : The coupling of quasi‐2D perovskite layers is demonstrated by Kai Wang, Rui Chen, Wallace C. H. Choy, and co‐workers in article number 2005570 . Their results show that a bifunctional ligand can simultaneously diminish the weak van der Waals gap and passivate perovskite defects for efficient energy transfer and radiative recombination. They fabricate blue PeLEDs that show high performance with an EQE of 10.11% and a long stability of 81.3 min.